KOMPETENSI GURU PAI DALAM MENGGUNAKAN MEDIA BERBASIS ICT PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS 4 SDN 017126 SEI TUALANG PANDAU - Rafika; Pakpahan, Rustam; Rasyid, Miswar (JIPIS, 2024)
This research is motivated by the researcher's interest in the use of ICT-based media by Islamic Religious Education teachers in Islamic Religious Education and Character Education learning in grade 4. Although the Islamic Religious Education teachers are part of the digital immigrant generation, which is generally considered less proficient in the use of technology, it turns out that they are able to overcome this challenge well. This study uses a qualitative research method using a descriptive approach, where the data collected by researchers is in the form of words or images obtained directly, does not emphasize numbers and really occurs naturally (natural setting), the data and facts found are then analyzed and presented so that they are easily understood by others. Data collection techniques use observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that the use of ICT media in learning at SDN 017126 Sei Tualang Pandau includes: learning through computer media, learning through multimedia and learning through communication technology. As for the pedagogical competence of Islamic Religious Education teachers at SDN 017126 Sei Tualang Pandau, it has been implemented well by Islamic Religious Education teachers by mastering every situation in the classroom during learning, such as mastering the characteristics of students, mastering learning theories and principles of educational learning, developing curriculum, organizing educational learning, utilizing information and communication technology, communicating with students effectively, empathetically and politely, and conducting assessments and evaluations of the learning process and results.